2016
DOI: 10.1177/0040517516679155
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the tensile and bending behavior of multi-axial warp-knitted fabric composites

Abstract: An experimental study was carried out on the tensile and bending behavior of multi-axial warp-knitted fabric composites. Five specimens reinforced with multi-axial warp-knitted fabric/epoxy were manufactured by a vacuum-assisted resin transfer molding method. Quasi-static tensile and three-point bending tests were carried out in a number of orientations relative to the stitching direction: quadriaxial, triaxial, biaxial (±45° and 0/90°) and unidirectional. The results of the tests revealed that the quadriaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…In Ref. , although V f is similar to that of this study, the type of the fiber is E‐glass fiber. Because the stiffness and the strength of the E‐glass fiber are less than those of the T700 carbon fiber, the mechanical properties of the corresponding composites are inevitably poorer.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In Ref. , although V f is similar to that of this study, the type of the fiber is E‐glass fiber. Because the stiffness and the strength of the E‐glass fiber are less than those of the T700 carbon fiber, the mechanical properties of the corresponding composites are inevitably poorer.…”
Section: Resultssupporting
confidence: 59%
“…performed three‐point bending tests to measure the flexural strength and the interlaminar shear strength of the warp‐knitted composites. Gao et al . analyzed the influence of the fiber orientation and the fiber volume fraction on bending behaviors experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The silane A-1387 content at 1.2wt% of epoxy hardener mixture was dispersed in the mixture. The 3DOWC was manufactured by means of Vacuum Assisted Resin Transfer Molding [22].…”
Section: Composite Preparationmentioning
confidence: 99%
“…In this part, the bending stress (s) and strain (e) were calculated according to equations (2) and (3). Then, the bending modulus was evaluated based on initial elastic part of bending stress and strain curve using equation (4) [22].…”
Section: Stress-strain Curvesmentioning
confidence: 99%
“…Wilhelmsson et al 3 found that the fiber waviness strongly impairs the compression behavior of composites and the maximum fiber misalignment can be used to accurately predict strength with analytical kinking criteria. Gao et al 4 fitted the tensile and bending stress–strain curves of the multiaxial warp-knitted composites (MWC) into a quadratic function relationship, which can be used to predict the stress corresponding to the strain. Yang et al 5 compared the compression property of 3-D orthogonal woven glass fiber composites with biaxial warp-knitted glass fiber composites and found that the compression strength of the former was 23.40% higher than that of the latter, and the modulus of the former was 4.9% lower than that of the latter.…”
Section: Introductionmentioning
confidence: 99%